Drugs in lactation. Issue 3 (20th January 2019) - Verstegen, Ruud H. J.; Ito, Shinya
Abstract: Although most medications can be taken safely during breastfeeding, potential risks of infant toxicity do exist because all medications will be excreted into the breast milk to some extent. The amount of medication excreted in the milk depends mainly on (i) within‐drug variation, such as dosing; (ii) between‐drug variation including chemical characteristics of the medication; and (iii) host factors, such as maternal pharmacokinetics (PK), including variations of pregnancy‐associated changes and their post‐partum recovery. Neonatal drug exposure is usually assessed by calculating an expected total infant daily dose through breast milk and comparing it to the normal therapeutic dose. However, clinical PK studies in this population are challenging to conduct. Recently, research methods using population PK analyses and physiologically‐based PK modeling and simulation techniques have been recognized as a complementary approach to the conventional PK studies in this field. These efforts are important for rational risk assessment balancing the toxicity risk against the benefits of human milk. Health benefits of lactation for both mother and child are significant and a decision to withhold from this should not be taken lightly. In case limited information is present, additional expertise from pharmacists or clinical pharmacologist with expertise in this area should be sought.